2015
DOI: 10.14302/issn.2372-6601.jhor-15-776
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Physical Activity Patterns In Patients With Thalassemia Compared To Healthy Controls

Abstract: Background: Patients with Thal (Thalassemia) are presumed to be inactive for many of the same

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…Additionally, pain in all body contributes to difficult in walking, running as well as doing light chores in home. The findings of Fung et al, (2015) (14) were congruent with present study who found that those children had reduced physical activities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, pain in all body contributes to difficult in walking, running as well as doing light chores in home. The findings of Fung et al, (2015) (14) were congruent with present study who found that those children had reduced physical activities.…”
Section: Discussionsupporting
confidence: 92%
“…Thalassemia is a chronic disease that presents a range of serious physical challenges as bone deformity, growth retardation, delayed puberty, short stature as well as poor self-image (13) . So, those children are presumed to be inactive (14) .The findings of the present study reflected that almost two thirds of the children had problems with usual physical activities and self-care which was supported by the findings reported by their parents. These results could be related to the regular period of mild anemia just prior to scheduled blood transfusion that limits their exercises capacity.…”
Section: Discussionsupporting
confidence: 86%
“…Anemia is known to contribute to poor appetite, and the slower rate of growth may also be related to higher rates of resting energy expenditure (and thus higher calorie/kg need) and a low hemoglobin level in the days preceding routine transfusions . However, overall energy expenditure may not be a significant drain, given a reduction in physical activity patterns . In toddlers, especially, parents may struggle with balancing adequate nutrition with a child's food preferences.…”
Section: Growth Deficiencymentioning
confidence: 99%
“…Reduced total caloric intake is also frequently observed in individuals with Thal, purportedly related to small stature [6] and reduced physical activity [7]. Decreased caloric consumption may increase the risk of nutritional deficits if an individual consumes a significant amount of “empty calories”, or foods with little nutritional value.…”
Section: Introductionmentioning
confidence: 99%